Tumor-Experienced Human NK Cells Express High Levels of PD-L1 and Inhibit CD8+ T Cell Proliferation - Sierra, Jessica M.; Secchiari, Florencia; Nuñez, Sol Y.; Iraolagoitia, Ximena L. Raffo; Ziblat, Andrea; Friedrich, Adrián D.; Regge, María V.; Santilli, M. Cecilia; Torres, Nicolás I.; Gantov, Mariana; Trotta, Aldana; Ameri, Carlos; et al. (Frontiers in Immunology, 2021)
Natural Killer (NK) cells play a key role in cancer immunosurveillance. However, NK cells from cancer patients display an altered phenotype and impaired effector functions. In addition, evidence of a regulatory role for NK cells is emerging in diverse models of viral infection, transplantation, and autoimmunity. Here, we analyzed clear cell renal cell carcinoma (ccRCC) datasets from The Cancer Genome Atlas (TCGA) and observed that a higher expression of NK cell signature genes is associated with reduced survival. Analysis of fresh tumor samples from ccRCC patients unraveled the presence of a high frequency of tumor-infiltrating PD-L1+ NK cells, suggesting that these NK cells might exhibit immunoregulatory functions. In vitro, PD-L1 expression was induced on NK cells from healthy donors (HD) upon direct tumor cell recognition through NKG2D and was further up-regulated by monocyte-derived IL-18. Moreover, in vitro generated PD-L1hi NK cells displayed an activated phenotype and enhanced effector functions compared to PD-L1- NK cells, but simultaneously, they directly inhibited CD8+ T cell proliferation in a PD-L1-dependent manner. Our results suggest that tumors might drive the development of PD-L1-expressing NK cells that acquire immunoregulatory functions in humans. Hence, rational manipulation of these regulatory cells emerges as a possibility that may lead to improved anti-tumor immunity in cancer patients.